2007
DOI: 10.1111/j.1440-1738.2007.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Sandstone diagenesis of the Lower Cretaceous Sindong Group, Gyeongsang Basin, southeastern Korea: Implications for compositional and paleoenvironmental controls

Abstract: The Gyeongsang Basin is a non-marine sedimentary basin formed by extensional tectonism during the Early Cretaceous in the southeastern Korean Peninsula. The sediment fill starts with the Sindong Group distributed along the western margin of the basin. It consists of three lithostratigraphic units: the Nakdong (alluvial fan), Hasandong (fluvial) and Jinju (lacustrine) formations with decreasing age. Sindong Group sandstones are classified into four petrofacies (PF) based on their detrital composition: PF-A cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Abouessa and Morad (2009) showed that siderite precipitated at high temperatures with high Fe and low Ca contents. High Fe/Ca (Table 3) also supports the interpretation of the precipitation of siderite cement within the early stage of diagenesis (Lee and Lim, 2008).…”
Section: Kaolinite Cementationsupporting
confidence: 54%
“…Abouessa and Morad (2009) showed that siderite precipitated at high temperatures with high Fe and low Ca contents. High Fe/Ca (Table 3) also supports the interpretation of the precipitation of siderite cement within the early stage of diagenesis (Lee and Lim, 2008).…”
Section: Kaolinite Cementationsupporting
confidence: 54%
“…Most Sindong Group sediments are thought to have been derived principally from metamorphic rocks, with some contributions from felsic plutonic and sedimentary rocks located to the west and northwest (Koh 1974). However, the upper half of the Jinju Formation contains a significant amount of volcanic detritus, mostly from syndepositional volcanoes (Choi 1986;Noh and Park 1990;Lee, Y.I. and Lim 2008).…”
Section: Geological Settingmentioning
confidence: 99%
“…31%) are subangular, and plagioclase is more abundant than K-feldspar. Plagioclases are mostly albitized and replaced partly by calcite (Noh and Park 1990;Lee, Y.I. and Lim 2008).…”
Section: Sandstone Petrographymentioning
confidence: 99%
“…Raised pre cip i ta tion tem per a tures for sid er ite are sup ported by high Mg and low Ca which are char acter is tic in sid er ite ce ment (Abouessa and Morad, 2009). Also, high Fe/Ca sup ports the in ter pre ta tion of the pre cip i ta tion of sider ite ce ment within the early stage of diagenesis (Berner, 1981;Lee and Lim, 2008). Also, geo chem i cal stud ies such as Estupinan et al (2007) in flu vial en vi ron ments showed that the pre cip i ta tion sid er ite as an early diagenetic min eral is com pat i ble with a low Sr con tent.…”
Section: Ta Blementioning
confidence: 99%